The Toileting Habit Profile Questionnaire-Revised: Examining Discriminative and Concurrent Validity. Issue 3 (3rd July 2019) - Beaudry-Bellefeuille, Isabelle; Lane, Alison; Chiu, Simon; Oldmeadow, Christopher; Ramos Polo, Eduardo; Lane, Shelly J
ABSTRACT: Sensory over-reactivity may be related to atypical defecation habits in children with constipation. The Toileting Habit Profile Questionnaire-Revised (THPQ-R) is designed to identify defecation-related sensory issues. This study examined the discriminative and concurrent validity of the THPQ-R. Differentiating between children with and without constipation was used to establish discriminative validity. The relationship between scores on the THPQ-R and on the defecation scale of the Virginia Encopresis-Constipation Apperception Test (VECAT-S) was examined to establish concurrent validity. The difference in THPQ-R scores was statistically significant. There was a strong positive correlation between the over-reactivity section of the THPQ-R and VECAT-S scores. Results support using the THPQ-R to identify atypical defecation behaviors.